Atividades práticas para a física no ensino fundamental por meio de desafios: proposta de material de apoio ao professor - Guariglia, Carlos Eduardo (2019)
According to Vygotsky's theory of learning, social relations are essential in the development of higher psychological functions. For him, it is through the guided relations with the world that the individual internalizes the knowledge and starts to develop such functions. Therefore, in his conception, group activities, or those in which the individual relates to others, are of great importance in cognitive development and learning. Moreover, in the search for a more focused physics teaching in the investigation and practical application of the concepts, we developed a sequence of activities seeking to privilege these aspects in the teaching-learning process. This work aims to present the development and study of a manual for the application of a sequence of activities, called "Creativity Challenges". These are composed of activities that aim to go beyond the theoretical contents traditionally addressed, seeking to promote the development of social-emotional skills, through constructions of prototypes and practices that involve experimentation and research.